P016 SZN-1326, a Wnt signal activator, is more efficacious than cyclosporine A in an acute DSS model. (27th May 2021) - Xie, L; Baribault, H; Lu, C; Handa, P; Newman, M; Le, L; Liu, A; Mutha, D; Deshmukh, S; Shah, D; Tun, C; Le, T; et al.
Abstract: Background: Current Inflammatory bowel disease (IBD) treatments focus on inhibition of excessive inflammation, and clinical remission rates have reached a plateau. There is a clear unmet need for agents that directly repair and regenerate the intestinal epithelial barrier as mucosal healing has been associated with reduced hospitalizations and long-term remission. Wnt/β-catenin signaling promotes intestinal stem cell renewal and is crucial for intestinal epithelial homeostasis and regeneration. Fzd5, a Wnt receptor, is highly expressed in intestinal epithelium. We have engineered a FZD5, 8 and LRP6 bi-specific IgG1 antibody, SZN-1326, which potently induced Wnt signaling in a Super Top Flash (STF) Luciferase reporter assay, stimulated intestinal organoid growth, increased Wnt target gene Axin2 expression in the colon tissue and ameliorated Dextran Sulfate Sodium (DSS)-induced colitis in mice. The objective of the current studies was to compare the efficacy of SZN-1326, a Wnt signal activator, to Cyclosporine A, which has been shown to have activity in an acute DSS-induced colitis mouse model. Methods: To induce acute colitis, 7- to 8-week-old female C57BL/6 mice were given drinking water containing 4.0% (w/v) DSS for 7 days followed by 1.0% DSS for 3 days. Groups of mice were treated either with an isotype control antibody (anti-GFP), one intraperitoneal (IP) injection of SZN-1326 at 2, 6, 20 mg/kg on day 4 or two injections of SZN-1326 at 1, 3, 10 mg/kg on days 4 and 7, or treated daily with Cyclosporine A by oral gavage at 80 mg/kg on days 0–9, and the mice were taken down on day 10. Results: Mice subjected to DSS developed severe colitis characterized by profound and sustained weight loss and bloody diarrhea, resulting in the increase of disease activity index (DAI). SZN-1326 treatments improved body weight, decreased fecal score, and reduced DAI much more effectively than Cyclosporine A. Histological evaluation showed SZN-1326 treatments repaired the damaged colon epithelium, decreased colon histology scores of inflammation, mucosal erosion, and goblet cell loss, at doses as low as 1 mg/kg dosed twice or a single dose of 2 mg/kg. In addition, SZN-1326 treatments significantly decreased serum levels of inflammatory cytokines, Lipocalin-2, IL-6 and IL-8, while Cyclosporine A treatment led only to a reduction of Lipocalin-2. Conclusion: In an acute mouse IBD model, SZN-1326 at various dosing regimen stimulated intestinal epithelial regeneration, induced mucosal healing and restored the epithelial barrier resulting in reduced inflammation, improved body weight and reduced disease activity. In contrast, Cyclosporine A showed only a mild effect on reducing DAI and lipocalin-2.